CA CONJUNCTIVE ADVERBS IN UNDERGRADUATE STUDENTS’ ARTICLES - Dawi Yanti (Acitya: Journal of Teaching and Education, 2019)
ABSTRACT: The main purpose of this study was to investigate conjunctive adverbs in undergraduate students’ articles. This study employed descriptive quantitative design which focused on the corpus analysis. The samples of the study were 73 articles selected from English department students’ articles at State University of Malang in the graduation academic year 2012/2013. After collecting all the articles, the researcher used the data that were classified into four types and the function was described using theory of conjunctive adverbs proposed by Halliday and Hasan; they are additive, adversative, causal and temporal. The instruments used to analyze the data were Ant.conc 3.41w sofware and interview guide. The results showed that there were 20 conjunctive adverbs in articles; causal categories (37%) were the mostly used by students writing, and then followed by adversative categories (26%), temporal categories (22%) and the last were additive categories (15%). The most frequent conjunctive adverbs was Because in causal categories which got 603 times (55.37%). Furthermore, the reason of students to choose conjunctive adverb Because as the most connectors used in the articles was because they think these conjunctive adverbs were the simplest and easiest connectors. Keywords: conjunctive adverbs, articles